Experimental study of hydrodynamics and soil responses around a sandbar and their effects on bed-level evolution - Mengyan Luo; Linlong Tong; Jisheng Zhang; Yakun Guo; Hao Wang; Ning Chen (Ocean Engineering, 2026)

Experimental study of the seabed responses induced by a floating column with a heave plate - Yiming Ji; Linlong Tong; Jisheng Zhang; Haoran Li; Hao Chen; Yakun Guo; Shoupeng Xie (Coastal Engineering, 2026)

Experimental study of soil liquefaction and wave damping during nonlinear waves and silty seabed interaction - Ning Chen; Linlong Tong; Jisheng Zhang; Hao Chen; Ji Peng; Yakun Guo (Ocean Engineering, 2026)

Pore pressure responses and seepage flow inside an unsaturated seabed caused by a floating cylinder - Linlong Tong; Yiming Ji; Jisheng Zhang; Hao Chen; Liangcai Wang; Shoupeng Xie; Yakun Guo (Ocean Engineering, 2026)

Hofmeister effect-assisted chain bundling and limited coalescence in Pickering emulsion to construct tough and conductive scaffolds for bone regeneration - Huan Tan; Linlong Li; Xue Bai; Yu Deng; Shichen Hu; Yuanyuan Zhou; Shirun Chu; Zili Guo; Jiahao Zhang; Hua Li; Jie Weng (Chemical Engineering Journal, 2025)

Statistical characteristics of turbulence in combined wave-current boundary layer flows - Xuan Zhang; Jinhai Zheng; Chi Zhang; Jisheng Zhang; Yakun Guo; Linlong Tong; Rupeng Wang; Haoran Li (Ocean Engineering, 2025)

Enhancement of PPCPs photodegradation in stormwater runoff by sulfur vacancy-induced ZnS1-x/ZnO on permeable concrete - Muzi Li; Xiaojuan Bai; Linlong Guo; Zhaoying Liu; Meipeng Jian; Chaohong Tan; Hongxiang Chai; Haiyan Li (Journal of Water Process Engineering, 2025)

Wave–Induced Soil Dynamics and Shear Failure Potential around a Sandbar - Ning Chen; Linlong Tong; Jisheng Zhang; Yakun Guo; Bo Liu; Zhipeng Zhou (Journal of Marine Science and Engineering, 2024)
Sandbars are commonly encountered in coastal environments, acting as natural protections during storm events. However, the sandbar response to waves and possible shear failure is poorly understood. In this research, a two–dimensional numerical model is settled to simulate the wave-induced sandbar soil dynamics and instability mechanism. The model, which is based upon the Reynolds-averaged Navier–Stokes (RANS) equations and Biot’s consolidation theory, is validated using available experiments. Parametric studies are then conducted to appraise the impact of the wave parameters and soil properties on soil dynamics. Results indicate that the vertical distribution of the maximum vertical effective stress in the sandbar is different from that in the flat seabed, which decreases rapidly along the soil depth and then increases gradually. The impact of soil permeability and saturation on the vertical effective stress distribution around the sandbar also differ from that in the flat seabed. Unlike the flat seabed, the vertical distribution of shear stress in the sandbar increases with an increasing wave period. The sandbar soil shear failure potential is discussed based upon the Mohr–Coulomb criterion. Results show that the range of shear failure around the sandbar is wider and the depth is deeper when the wave trough arrives.

Wave Motion and Seabed Response around a Vertical Structure Sheltered by Submerged Breakwaters with Fabry–Pérot Resonance - Lai Jiang; Jisheng Zhang; Linlong Tong; Yakun Guo; Rui He; Ke Sun (Journal of Marine Science and Engineering, 2022)
This paper presents the results from a numerical simulation study to investigate wave trapping by a series of trapezoidal porous submerged breakwaters near a vertical breakwater, as well as the seabed response around the vertical breakwater. An integrated model, based on the volume-averaged Reynolds-averaged Navier–Stokes (VARANS) equations is developed to simulate the flow field, while the dynamic Biot’s equations are used for simulating the wave-induced seabed response. The reflection of the wave energy over the submerged breakwaters, caused by the vertical breakwater, can be reserved, indicating that the existence of the submerged breakwaters in the front of the vertical breakwater can either provide shelter or worsen the hazards to the vertical breakwater. Numerical examples show two different modes under the Fabry–Pérot (F–P) resonance condition of the wave transformation, namely the wave reflection (Mode 1) and the wave trapping (Mode 2). The distance between the submerged breakwaters and the vertical breakwater, is a key parameter dominating the local hydrodynamic process and the resultant dynamic stresses around the vertical breakwater. The numerical results indicated that more submerged breakwaters and a higher porosity of submerged breakwaters will obviously dissipate more wave energy, and hence induce a smaller wave force on the rear vertical breakwater and liquefaction area around the vertical breakwater.